Advanced prodrug strategies in nucleoside analogues targeting the treatment of gastrointestinal malignancies - Xu, Xingxing; Li, Zixuan; Yao, Xueying; Sun, Nannan; Chang, Junbiao (Frontiers in Cell and Developmental Biology, 2023)
Gastrointestinal malignancies are common digestive system tumor worldwide. Nucleoside analogues have been widely used as anticancer drugs for the treatment of a variety of conditions, including GI malignancies. However, low permeability, enzymatic deamination, inefficiently phosphorylation, the emergence of chemoresistance and some other issues have limited its efficacy. The prodrug strategies have been widely applied in drug design to improve pharmacokinetic properties and address safety and drug-resistance issues. This review will provide an overview of the recent developments of prodrug strategies in nucleoside analogues for the treatment of gastrointestinal malignancies.